Peculiarities of industrial nature management in the conditions of modern decentralization - Nazaruk, Mykola; Halianta, Lidiia (Journal of Education, Health and Sport, 2021)
The aim of the study was to determine the features of industrial development in modern decentralization. Materials and methods. This study is based on the study of literature sources that characterize the problems of industrial nature management, features of development and operation, geospatial features of industry. The most well-known literary sources are analyzed, namely monographs, reporting materials, articles, reports concerning the problems of industrial nature management in the conditions of modern decentralization. Results. Decentralization contributes to the development of the economy, as the authorities respond more quickly to the demands and needs of society. Decentralization processes are improving the so-called investment climate, resulting in economic growth. That is why it is important to consider the factors influencing the development of industry in today’s decentralization. We highlight the political and legal, economic, socio-demographic, technological factors of industrial development. On their example, we will consider features of development of the industry in the conditions of modern decentralization. Conclusion. The analysis of development factors and structural transformations in industry has revealed a number of sharp contradictions that create many risks for the existence of the industry itself, as well as the economy and social sphere of the country. This poses a number of serious challenges to the country to overcome such contradictions as: the inconsistency of the general trend of the industry with the development of world industry in structural and technological terms; continuation of structural and organizational degradation of production with preservation of its export-raw material orientation and corresponding dependence on external conditions; increasing technological simplification and primitivization of production; inconsistency of domestic production with the needs of the population; the progressive decline of processing industries, including high-tech and fund-generating, for the domestic consumer market; high depreciation of fixed assets and unattractive investment of the industry, including for foreign investors; remoteness of the financial sector from servicing long-term investment needs of production; "Conservative" distribution of investment resources; lack of a mechanism for redistribution of investment resources in favor of promising industries. The identified contradictions and the resulting risks to the further functioning of the industry must be resolved as soon as possible for progressive changes and industrial development in the future.